Public Space Semiotics: Reading Visual Language in City Park Design - Muktiono, Ayub (GoAcademica Research & Publishing, 2024)
This research explores the semiotic dimensions of public space, specifically focusing on visual language in urban park design. The main aim of this research is to understand how visual elements in city parks can be interpreted as signs that create meaning in the context of public space. This research uses a qualitative approach with descriptive methods. The results of this research reveal that urban park designs that utilize a semiotic approach in analyzing design elements can create spatial experiences that are rich in meaning for visitors. The use of local and traditional symbols, plants native to the region, as well as modern or innovative architectural elements provide an additional dimension that goes beyond the purely physical aspects. Design that accommodates community diversity, pays attention to functionality, and shows concern for environmental sustainability creates public spaces that are inclusive and relevant to community needs. Thus, a semiotic approach not only helps understand the meaning behind urban park design, but also becomes a valuable guide for designing open spaces that are more meaningful and closely connected to the values and cultural identity of local communities.